2015
DOI: 10.4414/smw.2015.14087
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years’ experience with the Swiss data registry for assisted reproductive medicine: outcomes, key trends and recommendations for improved practice

Abstract: Optimal ovarian stimulation should be designed for the retrieval of 10 to 15 oocytes per treatment. Swiss legislation should enable and stimulate a policy of elective single embryo transfer to avoid multiple births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…retrieving three instead of two oocytes increases the predicted LBR by approximately 25%, relatively, in all age groups. Interestingly, this relative increase in LBR was also reported comparing PORs (< 5 oocytes) with suboptimal responders (5–9 oocytes) in a large retrospective study based on national registry data from 2005 to 2012 in Switzerland [ 27 ].…”
Section: One More Oocyte Matterssupporting
confidence: 56%
See 1 more Smart Citation
“…retrieving three instead of two oocytes increases the predicted LBR by approximately 25%, relatively, in all age groups. Interestingly, this relative increase in LBR was also reported comparing PORs (< 5 oocytes) with suboptimal responders (5–9 oocytes) in a large retrospective study based on national registry data from 2005 to 2012 in Switzerland [ 27 ].…”
Section: One More Oocyte Matterssupporting
confidence: 56%
“…The reason is most certainly the follicular synchronization obtained after down-regulation, which for the expected POR is of utmost importance as these patients usually have increased late luteal FSH levels during their natural cycle, promoting early recruitment of the leading follicle. As one more oocyte increases the live birth rate by 5% [ 26 , 27 ], the long GnRH agonist down-regulation protocol should be first line treatment for expected POR, unless a double stimulation [ 37 ] is planned for oocyte/embryo accumulation and subsequent frozen thaw embryo transfer.…”
Section: Icos In Expected Poor Responders (Poseidon Groups 3 and 4)mentioning
confidence: 99%
“…Of note, there were significant difference in the COH protocol and number of oocytes collected. It has been reported that different stimulation protocols (agonist vs. antagonist) (34) and the number of oocytes collected (35,36) may cause bias on the LBR. Hence, duration of infertility, the number of AFC, the number of oocytes collected, and COH protocol were adjusted in logistic regression along with other potential confounding factors.…”
Section: Interpretation Of Datamentioning
confidence: 99%
“…ART success has been commonly reported as the delivery of a live birth resulting from one initiated or aspirated ART cycle (7). The most comprehensive studies indicate that there is a positive association between the number of retrieved oocytes and live birth rates (LBR), in particular, cumulative LBR, with higher oocyte thresholds for better outcomes (8)(9)(10). Although the LBR is the preferable endpoint for couples, it depends on a multitude of controlled and uncontrolled factors, thus making it challenging to use this metric for individualized predictions about the number of oocytes needed to achieve the desired outcome.…”
Section: Introductionmentioning
confidence: 99%